Determinants of Participation in Manufacturing GVCs in Africa : The Role of Skills, Human Capital Endowment and Migration - Yameogo, Nadege D.; Jammeh, Kebba (World Bank, Washington, DC, 2019)
This analysis assesses the role of skills, human capital endowment, and migration as determinants of Sub-Saharan Africa's participation in manufacturing global value chains. Due to lack of reliable data on skilled labor, skilled and unskilled labor contents in exports were generated from the Global Trade Analysis Project database. A panel of 23 countries for which data on skills and manufacturing global value chains are available for 19 subsectors was constructed. A fixed-effect gravity model was used to estimate the determinants of backward and forward global value chain participation. The estimates obtained from the sample are compared with global data covering 115 countries for benchmarking purposes. The results indicate that for economies in Sub-Saharan Africa, skilled labor seems to be the strongest determinant of participation in backward and forward global value chains. Similarly, initial human capital endowment has a strong positive impact on global value chain participation at the global level. However, countries with relatively high initial capital endowment benefit more by incorporating foreign value-added products in their manufacturing exports. Finally, countries that receive net inflows of migrants tend to engage better in backward and forward global value chains than those with net outflows of migrants. The findings suggest that policies to improve Sub-Saharan Africa’s integration in manufacturing global value chains should target: shifting from unskilled to skilled labor-intensive backward and forward global value chain activities; upgrading the quality of the labor force, since unskilled workers are so far the most available and the most used in manufacturing global value chains; investing in the quality of human capital; and promoting intraregional skills mobility.